Is revisional surgery mandatory when an unexpected sarcoma diagnosis is made following primary surgery?. Issue 1 (December 2015) - Koulaxouzidis, Georgios; Schwarzkopf, Eugenia; Bannasch, Holger; Stark, G.
Abstract Background Soft tissue sarcomas (STS) are often diagnosed unexpectedly after surgery, and many excisions are incomplete. As histopathological assessments are challenging, patients later referred to comprehensive cancer centers (CCC) often come with an unclear status. This can make treatment planning problematic. We investigated the reliability of primary histopathological assessments, whether revisional surgery improved resection status, and the prognostic value of residual tumor at re-excision. Methods We analyzed the demographic and clinical characteristics of all patients referred to our CCC between 2003 and 2013. We compared patients treated exclusively at our CCC with those who had primary surgery elsewhere, and focused on resection margins, re-excision type, residual tumor, resection status after re-excision, and oncological outcome. Results Over half (n  = 110) of all patients (n  = 204) were referred from elsewhere. Seventy-one had undergone an excision without suspicion of malignancy. Resection status in referred patients was significantly inferior to the CCC group (p  < 0.0001), although the latter had significantly more serious tumors and advanced disease stages (p  < 0.05). The residual tumor rate was 53.13 %, with a significantly higher probability in an upper extremity (p  = 0.001). Initial histopathological classification was misleading in 46.9 % of cases. Re-excision improved resection status in 69 % of cases. Residual tumor presumably leads to higher rates of local recurrence (p  = 0.057) and significantly shorter times to recurrence (p  < 0.05). Conclusions Re-excision should always follow unplanned STS excisions. Resection margins and histopathological assessments from referring institutions are often unreliable and unsuitable for treatment planning. Residual tumor is a risk factor for earlier and more likely local recurrence.